Detection of anti-cell membrane DNA antibodies in SLE patients with indirect immunofluorescent and ELISA techniques - Awang Kechik, Faten Nurul Amira (2021)
Systemic lupus erythematosus (SLE) is known for its wide range of clinical manifestations. The diagnosis of SLE remains a challenge and to a great extent depends on multiple serum autoantibodies such as anti-nuclear antibody (ANA), anti-double stranded (ds) DNA antibody and anti-Smith antibody. ANA is a very sensitive but not specific marker and primarily use for SLE screening. Anti-dsDNA and anti-Sm are SLEspecific autoantibodies with lower sensitivity of 80% and 30% for SLE, respectively. A substantial percentage of SLE patients were found to be persistently negative for SLEspecific autoantibodies. It was reported to be as high as 51.2% for anti-dsDNA and 62.4% for anti-Sm. This impediment can delay the establishment of diagnosis and treatment. Therefore, researchers continue to search for other biomarkers that are better or able to complement the available standard SLE investigations. Cell membrane DNA (cmDNA) was identified as a specific target for autoantibodies in SLE patients. Autoantibodies towards cmDNA (anti-cmDNA) were shown to have promising value as an SLE biomarker. This study evaluated the potential of serum anti-cmDNA antibodies detection using indirect immunofluorescent (IIF) technique as a diagnostic marker in SLE. This study included serum samples of 83 SLE, 86 other connective tissue diseases (OCTD) and 61 healthy subjects. The OCTD samples were 56 rheumatoid arthritis, 12 scleroderma, 10 Sjogren’s syndrome and eight mixed connected tissues disease (MCTD). All samples were analysed by both IIF technique utilising Raji cells as substrate and ELISA for the presence of anti-cmDNA. For IIF, anti-cmDNA was reported as positive if there was presence of cell membrane continuous or punctate fluorescent ring. For ELISA, anti-cmDNA positivity was determined according to the cut-off value identified using ROC curve analysis. Serums from SLE patients were also tested for anti-dsDNA and anti-Sm antibodies using enzyme-immunoassays. These findings showed that anticmDNA positivity by IIF was the highest in SLE (55.4%) than in OCTD (9.3%) and healthy subjects (0%). Detection of anti-cmDNA using IIF technique showed high specificity in differentiating between SLE from healthy subject (100%) and OCTD (90.7%). The sensitivity of anti-cmDNA in differentiating between SLE from both groups was the same (55.4%). Anti-cmDNA was shown to be significantly associated with arthritis (p=0.019). However, no significant associations were found between anticmDNA and other SLE clinical presentations (mucocutaneous, serositis, lupus nephritis, neurological and haematological involvement). Despite, SLE-associated autoantibodies (ANA, anti-dsDNA and anti-Sm) were also more frequently seen in anti-cmDNA positive SLE, they were not statistically significant. In SLE with negative specific autoantibody, anti-cmDNA was detected in up to 52.1% of SLE patients with negative anti-Sm, 36.8% of SLE patients with negative anti-dsDNA and 31.3% of SLE patients with negative both anti-Sm and anti-dsDNA. Anti-cmDNA detection using ELISA was found to be more sensitive at 95.2% and 97.6% but less specific at 88.5% and 86.0% in differentiating SLE from healthy subjects and OCTD, respectively. In summary, IIF technique provided a high specificity for anti-cmDNA detection which makes it an excellent confirmatory tool for SLE diagnosis. ELISA technique on the other hand, is more suitable as a screening tool because it has better sensitivity. Anti-cmDNA also has the potential as a new additional biomarker to the current standard SLE autoantibodies especially in SLE with negative anti-dsDNA and/or anti-Sm antibodies.